The Curious Case of Carson McCullers: Appropriation, Allyship, and the Problem of Speaking for Others - Steele, Alexander (Disability Studies Quarterly, 2023)
In this article, I situate the life and work of Carson McCullers within the larger disability studies debate over the problem of speaking for others. The essay makes two arguments that build on one another. The first is for including McCullers more fully in the disabled community and in studies of literary disability, despite her having expressed a small number of ableist comments. The article suggests that McCullers’s experience as a queer disabled woman became a key lens that animated much of her writing. The essay then turns to its second and larger goal, which is to consider how the complicated case of McCullers can help the field distinguish allyship from appropriation and unethical identification. Turning to feminist theorists of communicative ethics Iris Marion Young and Linda Alcoff, as well as Deaf and disability scholars like Rebecca Sanchez, the article ultimately argues that McCullers’s “use” of deafness in The Heart Is a Lonely Hunter, though undeniably flawed, is not an act of appropriation but an early historical attempt at allyship from a differently disabled perspective. Her commitment to deafness is driven by a sustained critique informed by the shared afflictions of injustice, but one that also overall refuses to dissolve human difference or speak for deafness.